Solanum Procumbens-Derived Zinc Oxide Nanoparticles Suppress Lung Cancer In Vitro through Elevation of ROS - Ibrahim Ibrahim Abdel Aziz; Almaimani A. Riyad; Almasmoum A. Hussian; Ghaith M. Mazen; Moorthy Kannaiyan (Bioinorganic Chemistry and Applications)
Lung cancer is one of the cancers with high mortality rate. The current therapeutic regimens have only limited success rate. The current work highlights the potential of Solanum procumbens-derived zinc oxide nanoparticle (SP-ZnONP)-induced apoptosis in A549 lung cancer cells. Synthesized nanoparticles were confirmed by UV-Vis spectrophotometry, X-ray diffraction (XRD), dynamic light scattering analysis (DLS), scanning electron microscopy (SEM), Fourier transform infrared (FT-IR), and photoluminescence analysis. Lactate dehydrogenase (LDH), cytotoxicity, and cell viability assays revealed that the SP-ZnONP caused the cell death and the inhibition concentration (IC50) was calculated to be 61.28 μg/mL. Treatment with SP-ZnONPs caused morphological alterations in cells, such as rounding, which may have been caused by the substance’s impact on integrins. Acridine orange/ethidium bromide dual staining revealed that the cells undergo apoptosis in a dose-dependent manner, which indicates the cell death. Furthermore, reactive oxygen species (ROS) were examined and it was shown that the nanoparticles elevated ROS levels, which led to lipid peroxidation. In short, the SP-ZnONPs increase the level of ROS, which in turn causes lipid peroxidation results in apoptosis. On the other hand, the SP-ZnONPs decrease nitric oxide level in A549 cells in a dose-dependent manner, which also supports the apoptosis. In conclusion, SP-ZnONPs would become a promising treatment option for lung cancer.